"Building blocks and drawing figures is not the same": Neuropsychological bases of block design and Rey figure drawing in typically developing children. Issue 3 (3rd April 2021) - Zappullo, Isa; Conson, Massimiliano; Zoccolotti, Pierluigi; Trojano, Luigi; Senese, Vincenzo Paolo
ABSTRACT: Several studies investigated the neuropsychological bases of spatial construction in developmental samples. However, no study directly tested whether the pattern of the neuropsychological processes implied in spatial construction changed depending on whether a block building or a figure drawing task is considered. Here, we used the path analysis to test the direct and indirect effects of verbal abilities (naming and verbal knowledge), executive functions, figure disembedding and mental rotation on two classical spatial construction tasks: the Rey-Osterrieth Complex Figure (ROCF) and the Block Design (BD). We recruited a sample of 186 typically developing children (age range: 7–12 years). Results showed that ROCF copying was directly influenced by age and figure disembedding, and it was indirectly affected by executive functions, naming and verbal knowledge, whereas BD was influenced in a direct way by verbal knowledge, figure disembedding and mental rotation and indirectly affected by executive functions and naming skills. Moreover, the results showed a full measurement invariance of the path model between sexes, whereas only partial invariance was found for age. Thus, we tested the model in two age groups (age ranges: 7–9.5 and 9.6–12 years) and found that the relationships between the variables of the model changed across development. Although other variables might be relevant to spatial construction, the present findings demonstrate different neuropsychological bases of drawing figures and building blocks in typically developing children.